Leaving a legacy : increase your social impact - Peeters, Kaat, 1978-; Mohout, Omar, ....- (Brugge : Die Keure, 2020)
Increase your social impact: People want to change things, improve the world. Our mind cannot live without meaning. Just like the body asks for food. We all know that we have the leverage to make things happen. It's important to know what to do, but it's even more important to remember why you do what you do. Leaving a legacy is about impact surviving the erosion of time. About scaling and accelerating positive impact. Be ready to get inspired about leaving your own legacy. How do you leave a legacy? What drives a legacy? How about your legacy statement? And how about increasing your impact? Will you choose for scaling up, scaling deep, scaling out, or maybe even scaling down? Get carried away by the impact point of view and discover how you can increase the impact of your organisation too. This book reveals strategies of a diversity of organizations, from NPO's over associations, governmental and knowledge institutes to commercial organizations, who succeeded in increasing their social impact. Because no matter in what kind of organization you are spending your days, you too may leave a legacy that has improved our world socially or ecologically.
Keywords: Changemanagement; Verandermanagement